Site-specific strand breaks in RNA produced by (125)I radiodecay - Gaidamakova, Elena K. (Oxford University Press, 2002)
Decay of (125)I produces a shower of low energy electrons (Auger electrons) that cause strand breaks in DNA in a distance-dependent manner with 90% of the breaks located within 10 bp from the decay site. We studied strand breaks in RNA molecules produced by decay of (125)I incorporated into complementary DNA oligonucleotides forming RNA/DNA duplexes with the target RNA. The frequencies and distribution of the breaks were unaffected by the presence of the free radical scavenger dimethyl sulfoxide (DMSO) or by freezing of the samples. Therefore, as was the case with DNA, most of the breaks in RNA were direct rather than caused by diffusible free radicals produced in water. The distribution of break frequencies at individual bases in RNA molecules is narrower, with a maximum shifted to the 3′-end with respect to the distribution of breaks in DNA molecules of the same sequence. This correlates with the distances from the radioiodine to the sugars of the corresponding bases in A-form (RNA/DNA duplex) and B-form (DNA/DNA duplex) DNA. Interestingly, when (125)I was located close to the end of the antisense DNA oligonucleotide, we observed breaks in RNA beyond the RNA/DNA duplex region. This was not the case for a control DNA/DNA hybrid of the same sequence. We assume that for the RNA there is an interaction between the RNA/DNA duplex region and the single-stranded RNA tail, and we propose a model for such an interaction. This report demonstrates that (125)I radioprobing of RNA could be a powerful method to study both local conformation and global folding of RNA molecules.